2007
DOI: 10.1109/vetecs.2007.185
|View full text |Cite
|
Sign up to set email alerts
|

Performance of IEEE 802.11a in Vehicular Contexts

Abstract: A key component of intelligent transportation is the provision of adequate network infrastructure to support vehicleto-vehicle and vehicle-to-roadside communication. In this paper we report on performance evaluations carried out using the IEEE 802.11a protocol at 5.2 GHz between a moving vehicle and a fixed base station. We concentrate our evaluation on realistic urban speeds and environments, observing that performance at very low speeds is degraded due to the presence of null zones. We vary the modulation sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The general simulation parameters are as follows: each vehicle generates constant bit rate traffic using UDP datagrams (we chose UDP and not TCP for the same reasons stated in Cottingham et al (2007)). 512-byte datagrams were transmitted at a rate of four packets per second.…”
Section: Simulation Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general simulation parameters are as follows: each vehicle generates constant bit rate traffic using UDP datagrams (we chose UDP and not TCP for the same reasons stated in Cottingham et al (2007)). 512-byte datagrams were transmitted at a rate of four packets per second.…”
Section: Simulation Environmentsmentioning
confidence: 99%
“…This classification clarifies that, although safety applications have attracted special interest and require more scrutiny, other types of applications need to be attended as well. Also, as shown by authors such as Cottingham et al (2007), Jansons and Barancevs (2012) and Wellens et al (2007), vehicular ad hoc networks (VANETs) introduce complex dynamics that have not emerged in other types of MANETs. Due to this lack of solutions for non-safety applications, this paper targets unicast communications, which is required by non-safety applications in vehicular scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The first is knowledgebased and attempts to know, by measuring beforehand, the signal strengths of available wireless networks over a given area such as a city. This could involve physically driving around and taking these readings [10]. These measurements need to be taken in different seasonal contexts as the effects of foliage on wireless propagation are well known [11].…”
Section: Advancedmentioning
confidence: 99%
“…However, due to limits on the latency (or the number of retransmission attempts) at the link layer, the residual (post-ARQ) loss rates can be high as well, particularly in scenarios involving mobility. For example, for communication among fast-moving ground vehicles, it has been observed that post-ARQ loss rates can be high (20% or more) and also have high variance [2], [3]. Such high packet loss rates have serious implications on performance of TCP when used over wireless networks.…”
Section: Introductionmentioning
confidence: 99%